Postural Body Sway as Surrogate Outcome for Myelopathy in Adrenoleukodystrophy - van Ballegoij, Wouter J. C.; van de Stadt, Stephanie I. W.; Huffnagel, Irene C.; Kemp, Stephan; van der Knaap, Marjo S.; Engelen, Marc (Frontiers in Physiology, 2020)
Background: Myelopathy is the core clinical manifestation of adrenoleukodystrophy (ALD), which is the most common peroxisomal disorder. Development of therapies requires sensitive and clinically relevant outcome measures. Together with spastic paraparesis, balance disturbance is the main cause of disability from myelopathy in ALD. In this cross-sectional study, we evaluated whether postural body sway – a measure of balance – could serve as a surrogate outcome in clinical trials. Methods: Forty-eight male ALD patients and 49 age-matched healthy male controls were included in this study. We compared sway amplitude and sway path of ALD patients to controls. We then correlated the body sway parameters showing the largest between-group differences with clinical measures of severity of myelopathy. To correct for age, we performed multiple linear regression analysis with age and severity of myelopathy as independent variables. Results: All body sway parameters were significantly higher in patients than controls, with medium to large effect sizes (r= 0.43-0.66, p<0.001). In the subgroup of asymptomatic patients, body sway amplitude was also higher, but the difference with controls was smaller than for symptomatic patients (effect size r= 0.38-0.46). We found moderate to strong correlations between body sway amplitude and clinical severity of myelopathy (r=0.40-0.79, p<0.005). After correction for age, severity of myelopathy was a significant predictor of body sway amplitude in all regression models. Conclusions: These results indicate that postural body sway may serve as a surrogate outcome for myelopathy in ALD. Such outcomes are important to evaluate new therapies in clinical trials. Further longitudinal studies in this cohort are ongoing.